Resilience among Single Adult Female Refugees in Hamilton, Ontario - Newbold, Bruce; Chung, Karen; Hong, Ellie (Refuge: Canada's Journal on Refugees, 2013)
Single adult females remain among the most vulnerable of all refugee populations. However, there is a lack of research on supporting and empowering these women. There is a new interest in identifying factors that reinforce resilience and, ultimately, adjustment to the host country. In line with the current work on resilience, semi-structured, in-depth, personal interviews with single refugee women were conducted in the city of Hamilton, Ontario. A grounded theory approach revealed participants’ perspectives on the support received from religious or cultural communities, non-governmental organizations, and the government in terms of their perceived contribution to adaptation. Both informal and formal support, along with individual characteristics, were found to be crucial for reinforcing resilience among these refugees, reflective of a collective resilience model that moves beyond individual and community resilience. Future research should aim to investigate the perspectives of those who did not receive social support from shelters as well as to assess the efficacy of current refugee support services.